Species richness of epiphytic bryophytes: drivers across scales on the edge of the Mediterranean. Issue 1 (8th August 2013) - Medina, Nagore G.; Albertos, Belén; Lara, Francisco; Mazimpaka, Vicente; Garilleti, Ricardo; Draper, David; Hortal, Joaquín
<x xml:space="preserve">Abstract</x> Spatial variation in species richness is one of the most frequently studied topics on macroecology. However, the relative importance of the factors affecting richness across scales and their influence on some groups of small‐sized organisms, such as bryophytes, remain unclear. We evaluate the relative importance of biogeographic region, climate, topography, forest structure and abundance in shaping epiphytic bryophyte richness at both local (forest) and sample (trunk) scale on the boundary between the Atlantic and Mediterranean regions in NW Spain. For that purpose we used simple, multiple and partial regressions, hierarchical partitioning and partial least squares path analyses. Although climatic variables related to water availability during spring and summer were the most important predictors of bryophyte richness, their effects were moderated by winter temperature. Abundance, in contrast, was mostly related to forest structure. Biogeographic region was not significantly related to richness. Interestingly, forest richness was the best predictor of trunk richness. Our results highlight the importance of seasonal distribution of rainfall and temperatures and support that the richness of bryophyte communities is constrained by mesoscale climatic factors, in particular the interplay between water and energy availability. In contrast, abundance seems to be controlled by habitat characteristics. We also detected a strong top‐down structure between both scales of measurement evidencing a scaling down of the climatic effect: richness at the sample scale is controlled mainly by local richness and local richness is in turn controlled by climate, so mesoscale climatic gradients are indirectly limiting richness at the smallest scale.